The therapeutic potential of vasoactive intestinal peptide (VIP) in the treatment of Gram-negative sepsis - Askar, Basim Ali (2016)
Gram-negative bacteria are the most common cause of the sepsis and lipopolysaccharide (LPS) a major component of Gram-negative bacteria is known to be of major importance in the development of sepsis. Human infection with Salmonella, a Gram-negative bacterium, is associated with a number of cases of sepsis and is particularly important in childhood sepsis. During salmonellosis, monocytes and macrophages produce a number of different pro-inflammatory mediators such as TNF-α, IL-1α, IL-12, IL-18, IFN-γ, reactive nitrogen species and oxygen species. Although the production of these inflammatory mediators is required for resolution of bacterial infections, they are contraindicated in diseases such as sepsis. In the initial (acute) phase of sepsis a Systemic Inflammatory Response Syndrome (SIRS) occurs in which inflammatory mediators are produced in high concentration, which can lead to organ failure and death. The SIRS phase is then replaced by a Compensatory Anti-inflammatory Response Syndrome (CARS) phase which leads to immunosuppression. The CARS phase can lead to secondary infection and subsequent mortality within 28 days of hospital admission. To date, several studies have evaluated the role of vasoactive intestinal peptide (VIP) as an anti-inflammatory agent that may have therapeutic potential in septic patients both in vitro and in vivo. VIP has been shown to inhibit production of inflammatory mediators produced by human monocytes in response to LPS. The aim of the work described in this thesis was to investigate the therapeutic potential of VIP in sepsis using an ex vivo human monocytes model infected with viable Salmonella Typhimurium 4/74 (rather than LPS). The study shows that VIP (10-7 M) stimulates an increase in the numbers of Salmonella recovered from infected human monocytes (MOI = 10). In addition, VIP also increases the survival rate of human monocytes infected with Salmonella. These two results may suggest a detrimental effect of VIP during bacteraemia and sepsis, since monocyte death may be beneficial during sepsis and bacterial overgrowth could lead to further increased LPS (and other antigen) stimulation of the immune system. However, VIP did significantly decrease Salmonella and LPS-induced TNF-α, IL-1β and IL-6 in monocyte supernatants. VIP also had a positive effect on IL-10 production in human monocytes infected with Salmonella or stimulated with LPS. Whether this suggests a possible detrimental effect of VIP is unknown but septic patients with high serum IL-10/ low TNF-α concentration ratio have previously been shown to have a poor prognosis. Higher IL-10 concentrations in infected monocytes (due to VIP) could also increase the CARS phase of disease with increased immunosuppression. Flow cytometry and qPCR analyses showed that of all of the VIP receptors, VPAC1 was expressed most highly during Salmonella infection, or LPS stimulation, of human monocytes. Administration of VIP inhibited VPAC1 has been shown by many studies to be the most important receptor by which VIP inhibits production of inflammatory immune mediators, or increases IL-10 production from murine macrophages. Results in this thesis, therefore, suggested that Salmonella infection may promote VPAC1 expression and so provide a mechanism of inhibiting the production of inflammatory mediators in infected cells. This could then increase intracellular survival of Salmonella and provide a means of greater dissemination of the infection. To ascertain how increased VPAC1 expression on the surface of monocytes may be achieved, analysis of the expression of known intracellular endosomal and exosomal constituents was performed. Confocal laser microscopy, using specific antibodies, showed that VPAC1 on the monocyte cell membrane was internalised within early endosomes (measured by co-localisation of VPAC1 and EEA1) rather than being degraded within lysosomes (measured by immunoreactivity to LAMP1). VPAC1 is then transported via a Rab11A recycling endosome and packaged in the Trans-Golgi network (TGN), shown by co-localisation of VPAC1/Rab11A and the TGN marker (TGN46). VPAC1 was then associated with Rab3a and calmodulin. The function of these latter two proteins in the docking of exosomes to the cell membrane is well known, thus suggesting that Salmonella induced VPAC1 was also recycled to the cell membrane within exosomes. VIP inhibited the expression of both Rab3a and calmodulin but not the co-localisation of VPAC1 with these two proteins. Further studies then showed that a calmodulin agonist (CALP1) increased VPAC1 expression on the surface of monocytes, while a calmodulin antagonist (W-7) decreased expression of VPAC1 on the surface of monocytes. In conclusion, this thesis does present hitherto unknown data regarding Salmonella infection of human monocytes and the effects of VIP on infected monocytes. VIP has potential as an anti-sepsis therapy since it reduces the production of inflammatory mediators by Salmonella-infected and LPS-stimulated monocytes. However, the fact that VIP increases survival of infected human monocyte and increased growth of Salmonella in human monocytes may preclude its use in sepsis.